Design of Catechin-based Carbon Nanodots as Facile Staining Agents of Tumor Cells - Yaung Kwee; Alfinda Novi Kristanti; Nanik Siti Aminah; Mochamad Zakki Fahmi (Universitas Gadjah Mada, 2020)
Carbon nanodots (CNDs) have widely received great attention as a result of favorable optical, electrical, optoelectrical, biocompatible, and non-toxic properties these nanoparticles possess. However, the exploration of nanoparticle from natural raw material was limited. In present work, the carbon dots were produced from catechin isolated from Uncaria gambir through a simple and facile process. Carbon nanodots were further produced by the pyrolysis process of catechin, which allowed it for carbonization. Owing to its unique properties such as photoluminescence with an emission peak at 500 nm (lex = 380 nm), average size diameter about 5 nm and non-toxic; Cat-CNDs were incredibly potential for staining targeted tumor cells. The staining ability by confocal microscopy observations showed their green fluorescence images which meant that the CNDs easily penetrated HeLa cells via endocytosis. The resulting CNDs which were analyzed using some significant techniques approved that the prepared Cat-CNDs were tremendously dispersible and water-soluble, good colloidal stability, excellent biocompatibility, favorable hydrophilicity, high photostability, and non-toxicity.